Nitrogen‐Doped Carbon Composites with Ordered Macropores and Hollow Walls. Issue 44 (1st October 2021) - Yao, Wen; Chen, Jianmin; Wang, Yajing; Fang, Ruiqi; Qin, Ze; Yang, Xianfeng; Chen, Liyu; Li, Yingwei
Abstract: Metal‐organic frameworks provide versatile templates for the fabrication of various metal/carbon materials, but most of the derived composites possess only microspores, limiting the accessibility of embedded active sites. Herein, we report the construction of cobalt/nitrogen‐doped carbon composites with a three‐dimensional (3D) ordered macroporous and hollow‐wall structure (H‐3DOM‐Co/NC) using a single‐crystal ordered macropore (SOM)‐ZIF‐8@ZIF‐67 as precursor. During the pyrolysis, the interconnected macroporous structure of SOM‐ZIF‐8@ZIF‐67 is mostly preserved, whereas the pore wall achieves a solid‐to‐hollow transformation with Co nanoparticles formed in the hollow walls. The 3D‐ordered macroporous carbon skeleton may effectively promote long‐range mass transfer and the hollow wall can facilitate local accessibility of active sites. This unique structure can greatly boost its catalytic activity in the selective hydrogenation of biomass‐derived furfural to cyclopentanol, much superior to its counterparts without this well‐designed hierarchically porous structure. Abstract : Cobalt/nitrogen‐doped carbon catalysts with 3D‐ordered macroporous and hollow‐wall structures were successfully fabricated by using ordered macroporous ZIF‐8@ZIF‐67 single crystals as precursors. This unique porous structure can greatly enhance mass transfer and accessibility of active sites to boost catalytic activity in the selective hydrogenation of furfural.